Ecto-and Endo-Parasites in Rodents and Shrews From Four Habitats in Selangor and Negeri Sembilan, Malaysia - Sithambaram, Paramasvaran (2009)

(untitled)
The objectives of this study were to determine the rodent host species, to identify the parasites they harbor and to record those parasites that are of zoonotic importance. A total of 204 rodents were examined from four selected habitats in the states of Selangor and Negeri Sembilan, Malaysia. The rodents were captured alive from five urban sites in Kuala Lumpur, rice fields in Tanjung Karang, a coastal area in Port Dickson and a Primary Forest Reserve in Gombak, Selangor. Standard laboratory parasitological and statistical analyses were used. Fourteen different rodent species belonging to three different mammalian groups were identified. Rattus rattus diardii was the predominant rodent species (67%) trapped and examined. The study revealed 53.9 % of the rodents examined had at least one species of helminth. A total of 21 helminth species (7 cestodes, 12 nematodes, 1 trematode and 1 acanthocephala) were recovered. Gongylonema neoplasticum, Nippostrongylus braziliensis, Hepatojarkus malayae, Heterakis supomosa, Capillaria hepatica Raillietina sp. Hymenolepis nana, H.diminuta, Hymenolepis sp. and Taenia taeniaeformis were the predominant helminth species identified. The helminths of zoonotic importance: Capillaria hepatica, Rictularia tani, Angiostrongylus sp., Taenia taeniaeformis, Hymenolepis nana, H. diminuta, Raillietina sp, Moniliformis dubius, Armillifer moniliformis were also found. Trypanosoma sp. was the only blood parasite found in the 204 rodents examined. Fourty seven percent of the rodents were found to be infested with at least one of the 20 species of ecto-parasites recovered. The common ecto-parasites recovered were Laelaps nuttali, L. echidnanus, L. sculpturata, Polyplax spinulosa, Hoplopleura pacifica, Ixodes granulatus, Dermacentor sp. and Haemaphysalis sp. The ecto-parasites that are of human medical importance are Laelaps sp., Gahrlepia sp., Walchiella sp., Ornthonyssus bacoti, Haemaphysalis sp., Dermacentor sp., Ambloyomma sp. and Ixodes sp. and Xenopsylla cheopis. A total of 147 ecto-parasites (ticks, n=15, fleas, n= 31, lice, n=30 and mites, n=71) were recovered from the rodents. Rattus rattus diardii was found to harbour a wide range of ecto and endo-parasites some of which have been identified as zoonotic. There was no significant relationship between the sex of rodents and parasitic infestion. However, significant association was seen between ecto and endo-parasitic infection and habitats. Rodents from the urban habitats comparatively were found to harbour a wider range of parasites, some of which are of human medical importance.